Improved catalytic activity and stability of cellobiohydrolase (Cel6A) from the Aspergillus fumigatus by rational design. (14th September 2020) - Dodda, Subba Reddy; Sarkar, Nibedita; Jain, Piyush; Aikat, Kaustav; Mukhopadhyay, Sudit S
Abstract: Cheap production of glucose is the current challenge for the production of cheap bioethanol. Ideal protein engineering approaches are required for improving the efficiency of the members of the cellulase, the enzyme complex involved in the saccharification process of cellulose. An attempt was made to improve the efficiency of the cellobiohydrolase (Cel6A), the important member of the cellulase isolated from Aspergillus fumigatus ( Af Cel6A). Structure-based variants of Af Cel6A were designed. Amino acids surrounding the catalytic site and conserved residues in the cellulose-binding domain were targeted (N449V, N168G, Y50W and W24YW32Y). I mutant 3 server was used to identify the potential variants based on the free energy values (∆∆G). In silico structural analyses and molecular dynamics simulations evaluated the potentiality of the variants for increasing thermostability and catalytic activity of Cel6A. Further enzyme studies with purified protein identified the N449V is highly thermo stable (60°C) and pH tolerant (pH 5–7). Kinetic studies with Avicel determined that substrate affinity of N449V (Km =0.90 ± 0.02) is higher than the wild type (1.17 ± 0.04) and the catalytic efficiency (Kcat/Km) of N449V is ~2-fold higher than wild type. All these results suggested that our strategy for the development of recombinant enzyme is a right approach for protein engineering.